Starling house - Harrow, Alix E. (Tor, Tor Publishing Group, 2023)
"Eden, Kentucky, is just another dying, bad-luck town, known only for the legend of E. Starling, the reclusive nineteenth-century author and illustrator who wrote The Underland--and disappeared. Before she vanished, Starling House appeared. But everyone agrees that it's best to let the uncanny house--and its last lonely heir, Arthur Starling--go to rot. Opal knows better than to mess with haunted houses or brooding men, but an unexpected job offer might be a chance to get her brother out of Eden. Too quickly, though, Starling House starts to feel dangerously like something she's never had: a home. As sinister forces converge on Starling House, Opal and Arthur are going to have to make a dire choice: to dig up the buried secrets of the past and confront their own fears, or let Eden be taken over by literal nightmares. If Opal wants a home, she'll have to fight for it."--